Retention in care among HIV-infected women initiating ART during pregnancy: a cohort study - Phillips, Tammy (Department of Public Health and Family Medicine, 2015)
Background: Recent international guidelines call for universal use of triple-drug antiretroviral therapy (ART) in HIV-infected women during pregnancy and postpartum. There are however concerns regarding potentially high levels of non-adherence and/or loss to follow-up (LTF) that may attenuate the benefits of ART for HIV transmission and maternal health. We investigated missed visits and LTF among women initiating ART during pregnancy in Cape Town, South Africa. Methodology: A retrospective cohort study was conducted of women starting ART between January 2011 and September 2012, at a large primary care antenatal clinic. Eligible women were identified in prevention of mother-to-child transmission (PMTCT) services based on CD4 â‰¤350 cells/Î¼l, and women initiated a regimen of tenofovir, lamivudine and efavirenz. Women eligible for ART were either referred to general adult ART services nearby (January-December 2011) or received ART integrated into ANC services (January-September 2012). Outcomes were measured up to six months postpartum: (i) LTF (no attendance within 56 days of a scheduled visit) and (ii) missed visit (returning to care 14-56 days late for a scheduled visit).